Pelatihan Bahasa Inggris dan Pembukuan Keuangan bagi Masyarakat Desa Langko - Titik Ceriyani Miswaty; Syamsurrijal Syamsurrijal; M. Zaki Pahrul Hadi; Baiq Andriani Ulfa (Jurnal Pengabdian UNDIKMA, 2020)
Langko Village is now being one of the villages that currently becomes the focus of the central and local governments as a pilot village for ginger drink centers. In line with the government's focus, the demands which carried by ginger drink UMKM are getting bigger, one of which is the demand for UMKM to master English so that they are ready to communicate with foreign tourists who visiting Langko village. In addition, those UMKM are still unable to manage their finances report. For this reason, English language training activities and financial accounting were carried out so that the purpose of the village community, regional and central government could be realized, creating Langko village as a ginger drink center village. The participants who involved in this training are lecturers and students majoring in Accounting and English. with an intensive training method, twice a week for six months, with English material for conversation between sellers and buyers and basic accounting material. The results achieved in this training activity are Langko village community in general and the UMKM activists in particular can apply the skills acquired during the training and can manage their UMKM finances more regularly and independently. The involvement of students also contributed significantly to the sustainability of the training.